New Coefficient Inequalities for Certain Subclasses of Valent Analytic Functions - Murat Caglar; Erhan Deniz; Halit Orhan (Journal of Advances in Applied & Computational Mathematics, 2015)
The object of the present paper is to derive new coefficient inequalities for certain subclasses of p - valent analytic functions defined in the open unit disk U. Our results are generalized of the previous theorems given by J. Clunie and F.R. Keogh [1], by H. Silverman [3] and by M. Nunokawa et al. [2].